2021
DOI: 10.21162/pakjas/21.91
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-phenological characterization of grape (Vitis vinifera L.) germplasm grown in northern zones of Punjab, Pakistan

Abstract: This endeavor includes thirty grapes’ genotypes grown in northern zones of Punjab, Pakistan to determine similarities and dissimilarities in forty-four morphological traits according to the descriptor “International Plant Genetic Resources Institute (IPGRI)”. The relation between the genotypes was determined by principal component analysis (PCA), and similarity was worked out by using cluster analysis. The dendrogram divided the genotypes into two main groups with classes and subclasses. The variation present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…Berry weight (BrWT), berry length (BrL), and berry diameter (BrD) had negative correlations with the physical-chemical traits (SS, TA, and SS/TA). These results confirm those obtained by different authors that also studied correlations between variables in the grape crop (Akram et al 2021, Khalil et al 2017, Vujović et al 2017) and observed significant correlations of high magnitude between variables of the same category (for example, between yield components, bunch weight, and bunch size; berry weight and berry size and physical-chemical traits).…”
Section: Resultssupporting
confidence: 91%
“…Berry weight (BrWT), berry length (BrL), and berry diameter (BrD) had negative correlations with the physical-chemical traits (SS, TA, and SS/TA). These results confirm those obtained by different authors that also studied correlations between variables in the grape crop (Akram et al 2021, Khalil et al 2017, Vujović et al 2017) and observed significant correlations of high magnitude between variables of the same category (for example, between yield components, bunch weight, and bunch size; berry weight and berry size and physical-chemical traits).…”
Section: Resultssupporting
confidence: 91%